Comparative Performance Evaluation of Commercial Packing Materials for Malodorants Abatement in Biofiltration - Raquel Lebrero; Elisa Rodríguez; María Collantes; Carlos De Juan; Geir Norden; Kim Rosenbom; Raúl Muñoz (Applied Sciences, 2021)
Packing materials used in biofiltration of gaseous pollutants represent a key design parameter, as a proper selection might not only determine the adequate performance of the system but also its cost-effectiveness. This study systematically assessed and compared the performance of a conventional plastic carrier with that of two novel clay-based materials from SAINT GOBAIN for the abatement of a model odorous stream composed of H2S, methylmercaptan and toluene. The packing materials were tested in biotrickling filters, biofilters and a two-phase biotrickling filter. SAINT GOBAIN materials exhibited a higher adsorption potential under abiotic conditions, a higher buffer capacity and a superior performance compared to conventional plastic rings when implemented in biotrickling filters operating at gas residence times as low as 7.5 s. Among the materials tested in biofilters, Filtralite Air AC supported almost complete H2S and toluene removals at a gas residence time of 20 s, while successfully eliminating methylmercaptan at values of ~80%. Interestingly, under most of the conditions tested, clay-based materials also showed comparable pressure drop values than those of plastic rings.